Accounting Theory or Digests Meters and Dilatation of the «Decimetres»? (Economic journal of Lesya Ukrainka Volyn National University, 2015)
It highlights the problem of surface-lightweight compilation e.g. scientific publications on improving the accounting theories that are constructed by pseudoscientific pattern uncritical acceptance of the thesis, the alleged name of the course «Accounting Theory» became an anachronism, so it must be replaced by ephemeral «metatheory». It is noted that similar exercises compilations anything useful for the development of accounting theory does not contain, and on the contrary, reduce the study misleading. It carried out a critical examination of a number of identical pseudointerpretations that have not yet moved into nothingness, like to the recent proposals for a radical renewal of the accounting theory by means of profound comprehension of the difference between the far-fetched charges and expenses – synonymous. It emphasized the need for the disclosure of the philosophical categories of knowledge of theories of accounting, assessing, analyzing the key provisions and concepts, monographs, or at least the fundamental articles of the global level, and not be limited to two or three academic credentials publications and stencil inclusion of names in alphabetical clip scientists supposedly investigated this or thatproblem of accounting.
Keywords: accounting, accounting theory, metatheory, pseudoscientific interpretation, compilation, plagiarism